Blueprint : Haura Medic Healthcare "Back Pillow" / Ainin Sorfina Afizan - Afizan, Ainin Sorfina (2020)
Back Pillow is one of the products innovated by Haura Medic Healthcare which aims to help in improving and repairing one’s body posture and to help those who experienced back pain. Back Pillow is made from memory foam where the material suits well for people with back pain. Its ergonomic shape aids in repairing the spine posture and equally distributing the force of gravity across the spine. In addition, this Back Pillow is attached with adjustable and removable bag strap where the users can wear it anywhere and can also remove it during sleeping.